1989
DOI: 10.1177/004051758905901009
|View full text |Cite
|
Sign up to set email alerts
|

Pore Structure and Dyeability of Cotton Crosslinked with DMDHEU and with DHDMI

Abstract: The pore structures of cotton fabrics crosslinked to impart durable press performance with dimethyloldihydroxyethyleneurea (DMDHEU) and dihydroxydimethylimidaz olidinone ( DHDMI ) were compared using a reverse gel permeation chromatographic technique. Water soluble series of ethylene glycols and sugars were used to study the elution characteristics of columns prepared from these fabrics. From these data, dif ferences in pore size distribution in the control and modified cottons were elucidated. The results wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…Whereas untreated cotton is readily dyeable with anionic dyes, in the presence of salt, dyeing crosslinked cotton to a comparable deep shade is not possible unless the cellulose structure has been correctly modified. The crosslinked fibre is restricted from swelling under aqueous conditions, thereby preventing diffusion of relatively large dye molecules into the crosslinked substrate [16]. Several studies have examined possible improvements to the dyeability of crosslinked cotton using cationic additives and/or crosslinkers [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Whereas untreated cotton is readily dyeable with anionic dyes, in the presence of salt, dyeing crosslinked cotton to a comparable deep shade is not possible unless the cellulose structure has been correctly modified. The crosslinked fibre is restricted from swelling under aqueous conditions, thereby preventing diffusion of relatively large dye molecules into the crosslinked substrate [16]. Several studies have examined possible improvements to the dyeability of crosslinked cotton using cationic additives and/or crosslinkers [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…The results were interpreted in relation to the receptivity of these fabrics towards CI Direct Red 81. Although cross-linking reduced the accessible internal volume, samples reacted with DHDMI retained substantially more accessible internal volume across the entire range of pore sizes [218].…”
Section: Subsequent Dyeing Of Cross-linked Cottonmentioning
confidence: 94%
“…Factors influencing the dyeability of cross-linked cotton with direct dyes have been studied in more detail [217,218]. Cotton fabrics cross-linked with formaldehyde, dimethylolethyleneurea (DMEU) (42) and DMDHEU (43) were dyed with CI Direct Red 81 (12) and Blue 78 (21).…”
Section: Subsequent Dyeing Of Cross-linked Cottonmentioning
confidence: 99%
“…Those results strongly support the possibility that the crosslinking state and pore structure for DMDHEUaspartic acid might be different from that for DMDHEU. Many authors [4][5][6][7] have reported that the pore structures of the treated fabrics can be affected by varying the functional groups of crosslinking agents. However, detailed information about the pore structure for fabrics treated with DMDHEU-alpha-amino acids is lacking.…”
mentioning
confidence: 99%